The actants and the actors in the contemporany police novels O Colecionador de Ossos and Uma Janela em Copacabana - Massi, Fernanda (Laboratório Editorial FCL-UNESP, 2010)
From the concepts of actant and actor of greimasiana semiotic we analyzed the narrative route of two essential character of made for the police novel: the criminal and the detective in twenty two works. These works are police novel best sellers in Brazil in the first years of 21st century – from January 2000 of February 2007. To deepen our research we select two contemporary police noveld and applied greimasiana theory in the story, highlighting the actantial role played by the character and the actors that played these roles in the discursive level. Considering the traditional police novels, that copyed Edgar Allan Poe’s model created in the 19st century, the contemporary works are very different, mainly about the detective and the criminal. Our first proposal in this article is to demonstrate the importance of the actants and the actors alterations in the police novel and its consequences to this kind of text.